2019
DOI: 10.1108/jmtm-04-2019-0140
|View full text |Cite
|
Sign up to set email alerts
|

Lean manufacturing and operational performance

Abstract: Purpose Lean manufacturing (LM) constitutes a consolidated alternative that has been successfully used to increase company effectiveness and performance. However, different studies have shown that many companies that attempt to integrate LM into their manufacturing operations fail in their efforts. Recent studies have shown that soft practices are a key factor for a successful LM implementation. The purpose of this paper is to analyze an in-depth review of the different human-related lean practices (HRLP) refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 77 publications
(76 reference statements)
0
67
1
2
Order By: Relevance
“…The study revealed that task orientation leaders were more interested in incorporating LMP than relation orientation leaders. A study conducted by Hernandez-Matias et al ( 2019 ) in Spanish 202 manufacturing companies showed that Human-Related Lean Practices (HRLP) had a significant relationship with OP. By considering the above, the following hypothesis is formulated:…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study revealed that task orientation leaders were more interested in incorporating LMP than relation orientation leaders. A study conducted by Hernandez-Matias et al ( 2019 ) in Spanish 202 manufacturing companies showed that Human-Related Lean Practices (HRLP) had a significant relationship with OP. By considering the above, the following hypothesis is formulated:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies can avoid sudden machine breakdowns from the implementation of total preventive maintenance, which leads to reduced maintenance costs. Lean practices related to human re-sources leads to significant increases in operational performance in terms of waste reduction and flexibility (Hernandez-Matias et al, 2019). Greater employee involvement and empowerment represents essential HRM elements in achieving these performance improvements.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Quality management or TQM is another important aspect of lean manufacturing, which represents a set of interrelated initiatives to assure the quality of the products and the equipment used to manufacture them (Yang et al, 2011). The human resource aspect of lean has been largely addressed in earlier research as employee involvement and empowerment are essential elements of successful lean implementation (Dal Pont et al, 2008;Hernandez-Matias et al, 2019;Yang et al, 2011).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "Lean" was coined by researchers at the International Motor Vehicle Program at the Massachusetts Institute of Technology [14]. This term is generally associated with the automotive company Toyota [15]where the engineer Taichi ohno and the legendary shigeo shingo built the temple of the Toyota production TPS.…”
Section: Lean Maintenance 40: An Application Of the Iot Technology In The Facility Management Industrymentioning
confidence: 99%